Chemotherapeutic prospects of organic extracts of Bornetella nitida from Selayar Island - Soekamto N.H.; Bahrun; Okino T. (Kuwait Journal of Science)
In this study, we aimed to identify the chemotherapeutic potential of Bornetella nitida, a Dasycladacean that contains various phytochemicals. Phytochemical extraction was performed using gradient maceration with n-hexane, chloroform, ethyl acetate, and methanol. Additionally, toxicity tests as well as antioxidant activity, cytotoxicity, phytochemical, and molecular docking analyses against three main cervical cancer proteins were performed. The B. nitida extracts showed moderate toxicity with LC50 ranging from 116.06 to 713.12 μg mL−1. The free-radical scavenging activity of 2,2-diphenyl-1-picrylhydrazyl varied with solvent polarity, exhibiting IC50 values of 22.20, 87.77, 401.55, and 752.08 μg mL−1 when extracted using n-hexane, chloroform, ethyl acetate, and methanol, respectively. Meanwhile, the cytotoxicity against HeLa cells ranged from 281.09 to 1329.33 μg mL−1, with the highest activity shown by the ethyl acetate extract. Gas chromatography-mass spectrometry (GC-MS) analysis revealed the presence of phytochemicals with various bioactivities in the extract, such as L-ascorbic acid 2,6-dihexadecanoate, octadec-9-enoic acid, hexadecatrienoic acid, 2,4-bis(1,1-dimethylethyl)phenol, 9,12-octadecadienoic acid (Z,Z), 1,2-benzenedicarboxylic acid, 2,6,10-trimethyl-14-ethylene-14-pentadecene, and phytol. Docking studies implied that the compounds commonly interact well with the binding site of the target protein. Overall, our results indicate that B. nitida extracts especially ethyl acetate extract can be developed as chemotherapeutic agents. © 2024